2021
DOI: 10.1093/ptj/pzab227
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Geriatric Low Back Pain Based on Hip Characteristics With a 12-Month Longitudinal Exploration of Clinical Outcomes: Findings From Delaware Spine Studies

Abstract: Objective The purpose of this study is to identify geriatric chronic LBP subgroups based on the presence of potentially modifiable hip impairments, using Latent Variable Mixture Modeling (LVMM), and to examine the prospective relationship between these subgroups and key outcomes over time. Methods Baseline, 3-month, 6-month, and 12-month data were collected from a prospective cohort of 250 community-dwelling older adults with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…The impetus then for researchers is to compare such experiences with MEPLO; thereby, ascertaining construct validity, content validity, and opportunities to refine and calibrate the test. Second, participants in this study had a primary symptom of persistent LBP but recent work suggests pain at other body sites such as the hip can influence pain and function in older adults with LBP 59. Future studies will investigate MEPLO performance in the context of concomitant or widespread pain.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The impetus then for researchers is to compare such experiences with MEPLO; thereby, ascertaining construct validity, content validity, and opportunities to refine and calibrate the test. Second, participants in this study had a primary symptom of persistent LBP but recent work suggests pain at other body sites such as the hip can influence pain and function in older adults with LBP 59. Future studies will investigate MEPLO performance in the context of concomitant or widespread pain.…”
Section: Discussionmentioning
confidence: 98%
“…Second, participants in this study had a primary symptom of persistent LBP but recent work suggests pain at other body sites such as the hip can influence pain and function in older adults with LBP. 59 Future studies will investigate MEPLO performance in the context of concomitant or widespread pain. Third, MEPLO was deemed feasible in the laboratory setting but at just under 18 minutes, may not be feasible for all clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited for a prospective cohort study, conducted from March 2013 to December 2016; details regarding study procedures and recruitment strategies have been previously published 28. Participants were eligible for participation if they were between the ages of 60 to 85 years, cognitively intact, and had nonspecific CLBP (ie, pain intensity≥3/10, pain frequency≥4 d/wk, pain duration≥3 mo).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited for a prospective cohort study, conducted from March 2013 to December 2016; details regarding study procedures and recruitment strategies have been previously published. 28 Participants were eligible for participation if they were between the ages of 60 to 85 years, cognitively intact, and had nonspecific CLBP (ie, pain intensity ≥ 3/10, pain frequency ≥ 4 d/wk, pain duration ≥ 3 mo). Exclusion criteria were nonmechanical LBP symptomatology, lower extremity pain intensity greater than LBP intensity, current spinal or hip fractures, severely impaired ambulatory capacity requiring the use of a walker, diagnosis of a progressive neurological disorder, and terminal illness.…”
Section: Participantsmentioning
confidence: 99%
“…There is potential to optimize management and improve outcomes if subgrouping around underlying mechanistic biomarkers are used to inform and adapt patient management In other body regions, researchers have defined patient subgroups, 42 and demonstrated that targeted treatments for subgroup deficits have improved outcomes over a non-specific general approach. 4346 Studies exploring the development of treatment subgroups for RC tendinopathy are warranted. This mechanistic knowledge will enable the design of a stepped and matched treatment approach.…”
Section: Introductionmentioning
confidence: 99%